THE SOCIAL ECONOMY IN ROMANIA AND THE IMPACT OF NONREIMBURSABLE EUROPEAN FUNDS OVER THIS SECTOR - Marilena Petronela CRISTEA; Ion DONA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objective of this paper is to present the situation of the social economy in Romania. Through this work, we want to emphasize the role that non-reimbursable European funds have in the development of the social economy in Romania, by making a comparison between the state of social economy before the funding period of 2007 to 2013, the state of social economy after the funding period of 2007 to 2013, the difference been made by the results of the European funding for this section. It is based on the annual reports provided by Ministry of European Funds for Sectoral Operational Programme Human Resources Development 2007-2013, along with recent publications presenting the investigated topic. For the funding period of 2007 to 2013, the data have been processed into the following indicators: social economy structures created, people qualified or requalified in programs for vulnerable groups and the number of jobs created. After the implementation period of 2007 to 2013, the social economy sector has been improved by the foundation of approximately 1,400 social economy structures, by the qualification or requalification of over 130,000 vulnerable people and by creating over 12,000 jobs in the founded structures. As a conclusion, we consider that after the funding period of 2007 to 2013, the significant steps have been made, but the improvements still need to be made in approaching the people belonging to vulnerable groups, helping them fill the gaps that separate them from the majority population in terms of education, work culture and skills required on the labour market.